Assessment of γ-H2AX levels in circulating tumor cells from patients receiving chemotherapy - Garcia-Villa, Alejandra; Balsubramanian, Priya; Miller, Brandon; Lustberg, Maryam; Ramaswamy, Bhuvaneswari; Chalmers, Jeffrey (Frontiers in Oncology, 2012)
Circulating tumor cells (CTCs) are prognostic markers in a variety of solid tumor malignancies. The potential of CTCs to be used as a “liquid biopsy” to monitor a patient’s condition and predict drug response and resistance is currently under investigation. Using a negative depletion, enrichment methology, CTCs isolated from the peripheral blood of breast cancer patients with stage IV breast cancer undergoing DNA damaging therapy with platinum based therapy were enriched. The enriched cell suspensions, were stained with an optimized labeling protocol targeting: nuclei, cytokeratins 8, 18, and 19, the surface marker CD45, and the presence of the protein ɣ-H2AX. As a direct or indirect result of platinum therapy, double strand break of DNA initiates phosphorylation of the histone H2AX, at serine 139; this phosphorylated form is referred to as ɣ-H2AX. In addition to ɣ-H2AX staining in specific locations with the cell nuclei, consistent with previous reports and referred to as foci, more general staining in the cell cytoplamim was also observed in some cells suggesting the potential of cell apoptosis. Our study underscores the utility and the complexity of investigating CTCs as predictive markers of response to various therapies. Additional studies are ongoing to evaluate the diverse γ-H2AX staining patterns we report here which needs to be further correlated with patient outcomes